Prosody in speech as a source of referential information. Issue 4 (21st April 2018) - Tzeng, Christina Y.; Duan, Josephine; Namy, Laura L.; Nygaard, Lynne C.
ABSTRACT: Although prosody has primarily been assumed to convey information regarding linguistic structure and speakers' emotional state, increasing evidence suggests that prosody also conveys referential details. We examined the extent to which language users produce and infer information from prosodic correlates to perceptual details in the visual modality, specifically colour brightness. In Experiments 1 and 2, speakers labelled colours that varied in brightness with either familiar colour names (e.g. red; Exp. 1) or novel words (e.g. blicket; Exp. 2). Speakers used higher pitch, shorter duration, and higher amplitude for novel words, but not for familiar colour names, when labelling brighter versus darker shades. Listeners in Experiment 3 reliably inferred the intended target colour referent from the recorded utterances obtained in Experiment 2. Findings suggest that prosody reflects cross-modal correspondences between auditory and visual domains and, like a type of vocal gesture, provides an additional channel of information that resolves referential ambiguity.